Simultaneous Determination of Hydroquinone, Catechol and Resorcinol at Graphene Doped Carbon Ionic Liquid Electrode. (19th June 2012) - Ma, Li; Zhao, Guang-Chao
Abstract : A new composite electrode has been prepared with doping graphene into the paste consisting graphite and ionic liquid, n-octyl-pyridinum hexafluorophosphate (OPFP). This electrode shows an excellent electrochemical activity for the redox of hydroquinone (HQ), catechol (CC), and resorcinol (RS). In comparison with bare paste electrode, the redox peaks of three isomers of dihydroxybenzene can be obviously, simultaneously observed at graphene doping paste electrode. Under the optimized condition, the simultaneous determination of HQ, CC, and RS in their ternary mixture can be carried out with a differential pulse voltammetric technique. The peak currents are linear to the concentration of HQ, CC, and RS in the range form1 × 10 - 5 to4 × 10 - 4, 1 × 10 - 5 to3 × 10 - 4, and1 × 10 - 6 to1.7 × 10 - 4 mol L −1, respectively. The limits of detection are1.8 × 10 - 6 mol L −1 for HQ, 7.4 × 10 - 7 mol L −1 for CC, and3.6 × 10 - 7 M for RS, respectively.